Post-Harvest Losses of Vegetables Caused by Pests: A Review - Hasan, Wajid; G N, Shreevani; Kumari, Neha; Verma, Karan; Panigrahi, Chandan Kumar; Mohapatra, Priyadarshani (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Insect pests indeed present a major challenge to the storage and processing of vegetables, spices, and ornamentals. Insects, pests and diseases are the major biotic constraints to vegetable production. They not only degrade the quality of the products but also pose serious food safety risks and result in crop loss of about 10-30%. Some of the insect pest responsible for PHL in storage are cigarette beetle (Lasioderma serricorne), drug store beetle (Stegobium panicum), Potato Rubber Moth (Phthorimaea operculetta), sweet potato weevil (Cylus formicarius) red flour beetle (Tribolium castaneum), Indian meal moth, bean weevils (Acantboscelides spp.). The instant, pattern and causes of post-harvest loss specifically due to insect pests are studied. The review revealed that yield losses occur due to major, invasive and emerging insect pests in vegetable crops. For instance, Leucinodes orbonalis cause 70–75% damage in brinjal. Plutella xylostella cause 52% damage, and Pieris brassicae causes 42% damage in cabbage. Furthermore, Maruca vitrata causes 36% flower and pod damage in cowpea. Epilachna vigintioctopunctata cause 13–88% leaf damage in cowpea. Again, Eariasvitella, E. insulana is responsible for 35% damage in okra, Helicoverpa armigera causes 50–80% damage in tomato, Diaphinia indica cause 23% damage in cucumber and lastly, Thrips parvispinus cause 22.8 % and Polyphagotarsonemus latus cause 50% damage in Chillie. The paper highlighted the importance of grain crops in the global food supply, emphasizing the need to understand grain crop losses and implement efficient management strategies. Additionally, it underscored the essential role of grains in the human diet and the severe consequences of grain loss on food and nutrition security. The study is expected to offer valuable insights into the complexities of agricultural product losses, their effects on food and nutrition security and the specific importance of addressing losses in grain crops.